Demotion as a constructive dismissal under the industrial relations act 1967: a comparative study between the Malaysian law and the United Kingdom law / Natrah Mazman, Ahmad Fakhri Abu Samah and Dk. Harnidawati Awangku Ibrahim. - Mazman, Natrah; Abu Samah, Ahmad Fakhri; Awangku Ibrahim, Dk. Harnidawati (Faculty of Law, 2006)
The Industrial Relation Act 1967 aims to create industrial harmony among the relationship between the employee and the employer. It is noted that trade disputes deem to be in existence when there is a disagreement between the employer and employee in any organization. Basically, the terms of the contract of employment itself always caused conflict of issues which later results in a trade dispute especially when the terms and conditions is regarding dismissal which seldom occurred. Furthermore when it regards to a circumstances of a constructive dismissal, it become worst when it comes to the issue of demotion. The problem arise due to the provision that is stipulated under the Industrial Relation Act 1967 which only governed the remedy for dismissal 'without just cause and excuse' as to the right of representation or reinstatement. However, it does not specifically express the protection of situation of unfair dismissal as well as constructive dismissal. Over the years, the Court in deciding cases of demotion have looked at the fact of its circumstances whereby it vary from case to case, however, as for the current position, the Court agreed that the employee who had been constructively dismissed can also invoke Section 20 of the Industrial Relation Act 1967 if and only the employee can come up with an onus to prove that their dismissal is unfair and is done without 'just cause and excuse'. An employee who has been demoted can only invoke Section 20(1), if they are able to fulfil the requirement of unfair dismissal. However, up until now, there is an ambiguity exist over the characteristic of a demotion which amounts to constructive dismissal. As it is a matter of facts, the Court has reached the consensus to apply certain types of tests in examining whether demotion amounts to a constructive dismissal or not. Thus, this research will come up with a discussion over the characteristic and criteria for a demotion to become constructive dismissal, vise versa.